Tailoring active chemical environment of naphthoquinone‐based cathodes with rapid kinetics for aqueous batteries - Jun Guo; Shuang Song; Zhenyu Hu; Li Lin; Lianshan Sun; Qingshuang Wang; Jianxun Zhao; Peng Chen; Xinwei Wang; Heng Liu; Wanqiang Liu; Wei Liu; et al. (Carbon Energy, 2025)
Abstract Organic electrode materials (OEMs) have garnered great attention for aqueous Zn‐ion batteries (AZIBs) owing to their flexible designability and sustainable resources. However, the sluggish reaction kinetics and low active site utilization have strongly restricted their development due to the competitive coordination of H+ and Zn2+ in weakly acidic zinc electrolytes. Herein, we design a symmetric naphthoquinone‐based cathode, 2,3‐dimethoxynaphthalene‐1,4‐dione (DMeNQ), with rational functional groups to facilitate proton coordination chemistry and accomplish improved ability to capture with zinc ion. The carbonyl and methoxy groups on the DMeNQ construct hydrogen bond networks and serve as a “proton pump” to expedite proton conduction through the Grotthuss‐type mechanism. Density functional theory calculations have visualized the formation of “ion traps,” while in situ Raman spectra have tracked the reversible evolution of the active sites. Accordingly, the DMeNQ delivers a high capacity of 245 mAh g−1 (99.6% utilization of the active groups) and a long lifetime of 50,000 cycles at 40 C in AZIBs. In addition, the DMeNQ also possesses a superior rate capability of 85 mAh g−1 and a satisfactory cycle life of over 150,000 cycles at 400 C in proton batteries. Our results provide an effective pathway for high‐performance OEMs.